Resin composition and optical member

The resin composition, comprising a cycloolefin copolymer and fine strontium carbonate powder within a specific range, addresses the issues of high in-plane phase difference and haze in optical members, achieving improved viewing angle characteristics and transparency.

JP2025060366APending Publication Date: 2025-04-10UBE CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024024397
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-02-21
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing optical members made from cycloolefin resins exhibit high in-plane phase difference (Re) and haze, which affect their viewing angle characteristics and transparency, while also having positive birefringence that is not easily canceled.

Method used

A resin composition is developed containing a cycloolefin copolymer and a specific range of fine strontium carbonate powder (1.1 to 2.5 parts by mass per 100 parts by mass of cycloolefin resin), which helps in reducing in-plane phase difference (Re) and haze while maintaining low out-of-plane phase difference (Rth).

Benefits of technology

The resin composition effectively reduces in-plane phase difference (Re) and haze, while maintaining a low out-of-plane phase difference (Rth), thereby improving the viewing angle characteristics and transparency of the optical member.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060366000004
    Figure 2025060366000004
  • Figure 2025060366000001
    Figure 2025060366000001
  • Figure 2025060366000002
    Figure 2025060366000002
Patent Text Reader

Abstract

To provide a resin composition capable of forming an optical member having reduced in-plane retardation (Re) and haze while maintaining a low out-of-plane retardation (Rth) within a predetermined range.SOLUTION: A resin composition comprises an alkaline earth metal carbonate and a cycloolefin resin, wherein the content of the alkaline earth metal carbonate in the resin composition is 1.1 to 2.5 pts.mass based on 100 pts.mass of the cycloolefin resin, and the cycloolefin resin is a cycloolefin copolymer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and an optical member. [Background technology]

[0002] Cycloolefin resins are amorphous transparent resins with an excellent balance of optical properties and excellent heat resistance, making them suitable optical resins for the manufacture of optical components (see, for example, Non-Patent Document 1). It has been disclosed that optical components are molded using optical resins containing alkaline earth metal carbonate powder in order to suppress the occurrence of birefringence distribution when the optical components are used in a bent state (see, for example, Patent Document 1).

[0003] In order to improve the viewing angle characteristics of an optical component, it is necessary to reduce the out-of-plane retardation (Rth) and the in-plane retardation (Re). Also, the lower the haze calculated from the ratio of diffuse transmitted light to the total light transmission amount, the lower the turbidity and the higher the transparency of the optical component. That is, the lower the values ​​of the out-of-plane retardation (Rth), the in-plane retardation (Re) and the haze, the better the optical component.

[0004] As resins suitable for optical resin lenses, products using cyclic olefin-based cycloolefin polymers (COP) and cycloolefin copolymers (COC) dominate the market for small lenses for smartphones and other devices. COC has superior moldability and impact resistance compared to COP, and has a low polarizability due to the polymer of norbornene and ethylene in the resin composition. Moreover, it can achieve birefringence in addition to a high Abbe number (an index for evaluating the chromatic dispersion of transparent bodies) (see, for example, Non-Patent Document 2). For this reason, COC holds the top share in the resin lens market.

[0005] On the other hand, COP and COC have positive birefringence, although it is smaller than that of polycarbonate (PC), etc. It is desirable to offset the birefringence caused by stress due to the shape and conditions during molding by combining it with a material that has negative birefringence, etc. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2021-47402 [Non-patent literature]

[0007] [Non-Patent Document 1] Journal of the Imaging Society of Japan, Vol. 55, No. 2, 236-242 (2016) [Non-Patent Document 2] Polymer, Vol. 55, September, 739 (2006) Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention aims to provide a resin composition capable of forming an optical member having reduced in-plane retardation (Re) and haze while maintaining a low out-of-plane retardation (Rth) within a certain range, and an optical member obtained by molding the resin composition. [Means for solving the problem]

[0009] As a result of investigations conducted by the present inventors to solve the above problems, it has been found that a resin composition containing a specified cycloolefin resin and strontium carbonate fine powder within a specific range can form an optical component having reduced in-plane retardation (Re) and haze while maintaining a constant low out-of-plane retardation (Rth).

[0010] That is, the present invention is a resin composition containing an alkaline earth metal carbonate and a cycloolefin resin, wherein the content of the alkaline earth metal carbonate in the resin composition is 1.1 parts by mass to 2.5 parts by mass per 100 parts by mass of the cycloolefin resin, and the cycloolefin resin is a cycloolefin copolymer.

[0011] The present invention also relates to an optical member comprising an injection-molded article made of the above-mentioned resin composition. Effect of the Invention

[0012] According to the present invention, it is possible to provide a resin composition capable of forming an optical member having reduced in-plane retardation (Re) and haze while maintaining a low out-of-plane retardation (Rth) within a certain range, and an optical member obtained by molding the resin composition. [Brief description of the drawings]

[0013] [Figure 1] X-ray diffraction diagram of alkaline earth metal complex carbonate (CaxSr1-xCO3). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described in detail.

[0015] The resin composition of the present invention contains an alkaline earth metal carbonate and a predetermined cycloolefin resin. The cycloolefin resin is a cycloolefin copolymer. The positive intrinsic birefringence of the cycloolefin copolymer is offset by the addition of the alkaline earth metal carbonate, so that a molded article having a birefringence close to zero can be produced.

[0016] (Alkaline earth metal carbonates) The alkaline earth metal carbonate is mainly composed of alkaline earth metal carbonate in the form of fine powder. The term "main component" means that the alkaline earth metal carbonate may contain auxiliary components such as a surface treatment agent in addition to the alkaline earth metal carbonate, and means that the alkaline earth metal carbonate is contained in an amount of, for example, 80 mass% or more. Hereinafter, the alkaline earth metal carbonate may be referred to as alkaline earth metal carbonate fine powder. The alkaline earth metal carbonate fine particles have an average major axis in the range of 10 to 100 nm, preferably in the range of 15 to 75 nm. If the average major axis is less than 10 nm, the particles are too small and tend to aggregate, which tends to deteriorate the dispersibility. On the other hand, if the average major axis is more than 100 nm, the particles are too large and tend to deteriorate the transparency when mixed with a resin.

[0017] The alkaline earth metal carbonate fine powder preferably has an aspect ratio (ratio of average major axis / average minor axis) of 1.1 or more, more preferably in the range of 1.2 to 5.0, and particularly preferably in the range of 1.3 to 4.0. The alkaline earth metal carbonate fine powder also preferably has an average diameter of 10 nm to 100 nm.

[0018] The average major axis and the average minor axis of the alkaline earth metal carbonate fine powder can be measured by visual inspection or automatic image processing of a SEM (scanning electron microscope) photograph of the alkaline earth metal carbonate fine powder. The major axis of the alkaline earth metal carbonate fine powder can be measured as the length in the longitudinal direction (length of the long side) when the alkaline earth metal carbonate particle is regarded as a rectangle.

[0019] The minor axis of the alkaline earth metal carbonate fine powder can be measured as the length in the short direction (the length of the short side) when the alkaline earth metal carbonate is considered as a rectangle. Specifically, a rectangle that circumscribes the alkaline earth metal carbonate particle in the image and has the smallest area is calculated, and the major axis and minor axis are obtained from the lengths of the major and minor sides. The "average" refers to the average value obtained by measuring the major axis and minor axis of a statistically reliable number (N number) of alkaline earth metal carbonate particles, and the number is usually 100 or more, preferably 300 or more, and more preferably 500 or more.

[0020] The alkaline earth metal carbonate fine powder includes magnesium carbonate fine powder, calcium carbonate fine powder, strontium carbonate fine powder, and barium carbonate fine powder. These alkaline earth metal carbonate fine powders may be used alone or in combination of two or more. The alkaline earth metal carbonate fine powder is preferably strontium carbonate fine powder.

[0021] The alkaline earth metal carbonate may be a composite carbonate containing two or more kinds of alkaline earth metals. Examples of the composite carbonate include Ca x Sr 1-x CO3 Aragonite-type carbonates with compositions represented by (0.1≦x<0.5) and Ba x Sr 1-x CO 3 The composition includes the following.

[0022] Ca x Sr 1-x CO 3 In aragonite-type carbonates with a composition expressed as (0.1≦x<0.5), when x is less than 0.1, there are many particles with an aspect ratio of less than 2.0, and when x is 0.5 or more, there are many particles with a different phase, CaCO 3 (calcite) is more abundant. The preferred range of x is 0.15≦x≦0.4, and the more preferred range is 0.2≦x≦0.335. The presence of Ca in carbonates can be confirmed by energy dispersive X-ray spectroscopy (EDS).

[0023] The alkaline earth metal carbonate fine powder may be further surface-treated with a surfactant. The alkaline earth metal carbonate fine powder surface-treated with a surfactant has improved dispersibility. When the alkaline earth metal carbonate fine powder itself does not require dispersibility, such as when the alkaline earth metal carbonate fine powder is mechanically dispersed during the production of the alkaline earth metal carbonate fine powder-containing resin composition, the alkaline earth metal carbonate fine powder does not need to be surface-treated with a surfactant.

[0024] As the surfactant, a compound having either a hydrophilic group or a hydrophobic group, preferably having a hydrophilic group and a hydrophobic group, and further having a group that forms an anion in water can be used. This compound is preferably a compound in which the hydrophilic group is a polyoxyalkylene group, one end of which is bonded to a hydrophobic group, and the other end of which is bonded to a group that forms an anion in water. The hydrophobic group is preferably an alkyl group or an aryl group, more preferably a phenyl group. The group that forms an anion in water is preferably a carboxylate group, a sulfate group, or a phosphate group.

[0025] The surfactant is preferably a phosphoric acid ester in which the group that forms an anion in water is a phosphoric acid group. Since phosphoric acid esters have higher heat resistance than carboxylates and sulfates, polymer compositions to which alkaline earth metal carbonate fine powders that have been surface-treated with phosphoric acid esters have been added are less likely to be discolored due to thermal decomposition of the surfactant. Examples of phosphoric acid esters include polyoxyethylene styrenated phenyl ether phosphate esters and polyoxyethylene alkyl ether phosphate esters.

[0026] The amount of surfactant attached to the surface of the alkaline earth metal carbonate fine powder is generally in the range of 1 to 40 parts by mass, preferably 3 to 30 parts by mass, per 100 parts by mass of the alkaline earth metal carbonate fine powder. If the amount of surfactant is too small, it may be difficult to obtain the effect of improving dispersibility. On the other hand, if the amount of surfactant is too large, the surfactant may become a foreign matter during the production of a resin composition containing the alkaline earth metal carbonate fine powder, causing a decrease in the visible light transmittance of the resulting resin composition or an increase in haze. The content of the surfactant in the alkaline earth metal carbonate fine powder can be measured, for example, by TG-DTA (thermogravimetric differential thermal analyzer).

[0027] (Method for producing alkaline earth metal carbonate) The method for producing the alkaline earth metal carbonate fine powder is described below. The alkaline earth metal carbonate fine powder can be produced, for example, by a method including a reaction step of reacting an alkaline earth metal hydroxide with carbon dioxide in the presence of a crystal growth inhibitor to produce alkaline earth metal carbonate particles, an aging step of growing the alkaline earth metal carbonate particles into needle-like shapes, a surface treatment step of treating the alkaline earth metal carbonate particles with a surfactant, and a drying step of drying the alkaline earth metal carbonate particles.

[0028] (Reaction process) In the reaction step, it is preferable to introduce carbon dioxide gas into a raw material liquid containing a crystal growth inhibitor and an alkaline earth metal hydroxide while stirring the raw material liquid, thereby carbonating the alkaline earth metal hydroxide to generate alkaline earth metal carbonate particles. The raw material liquid may be an aqueous solution in which an alkaline earth metal hydroxide is dissolved, or an aqueous suspension in which an alkaline earth metal hydrate is dispersed. The concentration of the alkaline earth metal hydroxide in the raw material liquid is not particularly limited, but is usually in the range of 1% by mass to 20% by mass, preferably in the range of 2% by mass to 18% by mass, and more preferably in the range of 3% by mass to 15% by mass.

[0029] The crystal growth inhibitor is a carboxylic acid having a hydroxyl group that adheres to the generated alkaline earth metal carbonate particles and inhibits the crystal growth of the alkaline earth metal carbonate particles. The crystal growth inhibitor is preferably an organic acid having two carboxyl groups and a total of 3 to 6 hydroxyl groups and dicarboxylic acids. Dicarboxylic acids or anhydrides thereof containing one or more hydroxyl groups in the molecule are more preferable. The crystal growth inhibitor may be a monomer that is a raw material for the optical resin to which the alkaline earth metal carbonate fine powder is added. The content of the crystal growth inhibitor in the raw material liquid is generally in the range of 0.1 to 20 parts by mass, preferably 1 to 10 parts by mass, per 100 parts by mass of the hydroxide of the alkaline earth metal.

[0030] The temperature of the raw material liquid is preferably within a range of 5° C. to 60° C. The flow rate of carbon dioxide gas introduced into the raw material liquid is generally within a range of 0.5 mL / min to 200 mL / min, preferably 0.5 mL / min to 100 mL / min, per 1 g of alkaline earth metal hydroxide.

[0031] The particle shape of the alkaline earth metal carbonate particles produced in the reaction step is not particularly limited and may be granular or acicular. The particle shape and size of the alkaline earth metal carbonate particles can be adjusted by conditions such as the liquid temperature of the raw material liquid, the concentrations of the alkaline earth metal hydroxide and monomer in the raw material liquid, and the flow rate of carbon dioxide gas introduced into the raw material liquid. When the alkaline earth metal carbonate particles produced in the reaction step are acicular, the following aging step may be omitted.

[0032] (ripening process) In the aging step, the aqueous suspension of alkaline earth metal carbonate particles obtained in the reaction step is preferably heated and aged at a temperature in the range of 75°C to 115°C to grow the alkaline earth metal carbonate particles into needle-like particles. If the heating temperature is less than 75°C, the crystal growth of the long axis of the alkaline earth metal carbonate particles is insufficient, and the average aspect ratio tends to be low. On the other hand, if the heating temperature exceeds 115°C, the crystal growth of the short axis of the alkaline earth metal carbonate particles is promoted, and the aspect ratio tends to be low. The heating temperature is preferably in the range of 80°C to 110°C, and particularly preferably in the range of 85°C to 105°C. Heat aging is preferably performed while stirring. The heating time is not particularly limited, but is usually in the range of 1 hour to 100 hours, preferably in the range of 5 hours to 50 hours, and particularly preferably in the range of 10 hours to 30 hours.

[0033] (Surface treatment process) In the surface treatment step, it is preferable to add a surfactant to the slurry of acicular alkaline earth metal carbonate particles obtained in the aging step, and treat the surfaces of the alkaline earth metal carbonate particles with the surfactant to obtain an aqueous slurry of highly dispersible acicular alkaline earth metal carbonate particles. After adding the surfactant to the slurry, it is preferable to stir the slurry to make the concentration of the surfactant uniform, and then apply shear force to the slurry. By applying shear force to break up the aggregated particles of the alkaline earth metal carbonate particles, it is possible to uniformly treat the surfaces of the alkaline earth metal carbonate particles (primary particles) with the surfactant. The amount of surfactant added to the slurry is generally in the range of 1 part by mass to 40 parts by mass, preferably 3 parts by mass to 30 parts by mass, relative to 100 parts by mass of the alkaline earth metal carbonate particles in the slurry.

[0034] (drying process) In the drying step, the aqueous slurry of highly dispersible acicular alkaline earth metal carbonate particles obtained in the surface treatment step is dried to obtain an alkaline earth metal carbonate. The drying step can be carried out by a known drying method using a dryer such as a spray dryer or a drum dryer.

[0035] (Cycloolefin resin) Cycloolefin resins are polymers having an alicyclic structure in their structural units. Cycloolefin resins are polymers having an alicyclic structure in the main chain, polymers having an alicyclic structure in the side chain, polymers having alicyclic structures in the main chain and the side chain, and mixtures of two or more of these in any ratio. Among these, polymers having an alicyclic structure in the main chain are preferred from the viewpoint of mechanical strength and heat resistance.

[0036] Examples of the alicyclic structure include saturated alicyclic hydrocarbon (cycloalkane) structure and unsaturated alicyclic hydrocarbon (cycloalkene, cycloalkyne) structure. Among these, from the viewpoint of mechanical strength and heat resistance, cycloalkane structure and cycloalkene structure are preferred, and cycloalkane structure is more preferred. In the present invention, cycloolefin copolymer, which is a cyclic olefin copolymer having an alicyclic structure and an aliphatic structure, is suitable. Cycloolefin copolymer is represented by the following general formula, for example.

[0037] [ka]

[0038] In the above general formula, x and y each represent a positive integer.

[0039] Cyclic olefin copolymers are copolymers of cyclic olefins and α-olefins, and are synthesized by addition copolymerization of cyclic olefins and α-olefins. They are copolymers of cyclic olefins and α-olefins rather than homopolymers of cyclic olefins because homopolymers of cyclic olefins are crystalline resins, and the transparency is impaired by diffuse reflection between the crystalline and amorphous parts. Copolymers of cyclic olefins and α-olefins are amorphous resins and exhibit transparency. Cycloolefin copolymers belong to the cyclic olefin copolymers, and are copolymers of norbornene-based cyclic olefins and ethylene.

[0040] The number of carbon atoms constituting the alicyclic structure is preferably 4 or more and 30 or less per alicyclic structure. When the number of carbon atoms constituting the alicyclic structure is within this range, the molded product has a good balance of mechanical strength, heat resistance, and moldability. The number of carbon atoms constituting the alicyclic structure is more preferably 5 or more, particularly preferably 6 or more, more preferably 20 or less, particularly preferably 15 or less per alicyclic structure.

[0041] In the cycloolefin resin, the ratio of the structural unit having an alicyclic structure is preferably 50% by weight or more. When the ratio of the structural unit having an alicyclic structure in the cycloolefin resin is within this range, the transparency and heat resistance of the molded product are good. The ratio of the structural unit having an alicyclic structure is more preferably 70% by weight or more, and particularly preferably 90% by weight or more.

[0042] Specific examples of the cycloolefin resin include norbornene polymers, monocyclic olefin polymers, cyclic conjugated diene polymers, vinyl alicyclic hydrocarbon polymers, and hydrogenated products thereof. Among these, norbornene polymers and hydrogenated products thereof are more preferred from the viewpoints of transparency and moldability.

[0043] Examples of norbornene-based polymers include ring-opening polymers of monomers having a norbornene structure and their hydrogenated products; addition polymers of monomers having a norbornene structure and their hydrogenated products. Examples of ring-opening polymers of monomers having a norbornene structure include ring-opening homopolymers of one type of monomer having a norbornene structure, ring-opening copolymers of two or more types of monomers having a norbornene structure, and ring-opening copolymers of a monomer having a norbornene structure and any monomer that can be copolymerized therewith.

[0044] Further, examples of the addition polymer of a monomer having a norbornene structure include an addition homopolymer of one type of monomer having a norbornene structure, an addition copolymer of two or more types of monomers having a norbornene structure, and an addition copolymer of a monomer having a norbornene structure and any monomer copolymerizable therewith. Examples of these polymers include the polymers disclosed in JP-A-2002-321302 and the like. Among these, the hydrogenated product of a ring-opening polymer of a monomer having a norbornene structure is particularly suitable from the viewpoints of transparency, moldability, heat resistance, low moisture absorption, dimensional stability, and light weight. Specific examples of cycloolefin resins include "ARTON" (registered trademark) manufactured by JSR Corporation; "APEL" (registered trademark) manufactured by Mitsui Chemicals, Inc.; and "TOPAS" manufactured by TOPAS ADVANCED POLYMERS.

[0045] Among them, cycloolefin copolymers having alicyclic and aliphatic structures are synthesized by direct addition polymerization of norbornene monomers and ethylene. This resin has excellent transparency, heat resistance that can withstand the usage environment and processing conditions, and especially exhibits high refractive index and low birefringence, making it an advantageous optical material among similar resins. In the present invention, cycloolefin copolymer (COC) is used as the cycloolefin resin.

[0046] The number average molecular weight of the cycloolefin resin (cycloolefin copolymer), in terms of polystyrene, measured by GPC (gel permeation chromatography) using a toluene solvent, is 10,000 to 200,000, preferably 15,000 to 100,000, and more preferably 20,000 to 50,000. The glass transition temperature of the cycloolefin resin is preferably 80°C or higher, and more preferably 100 to 250°C.

[0047] The resin composition of the present invention can be prepared by mixing the above-mentioned cycloolefin resin (COC) and alkaline earth metal carbonate fine powder. The content of the alkaline earth metal carbonate fine powder is specified to be 1.1 to 2.5 parts by mass relative to 100 parts by mass of the cycloolefin resin. By injection molding such a resin composition, an injection molded article can be manufactured in which the in-plane retardation (Re) and haze are reduced while maintaining a low out-of-plane retardation (Rth) in a certain range. The content of the alkaline earth metal carbonate fine powder is preferably 1.25 to 2.25 parts by mass, more preferably 1.25 to 2.0 parts by mass, and even more preferably 1.25 to 1.75 parts by mass relative to 100 parts by mass of the cycloolefin resin.

[0048] In the manufacture of injection molded products, first, alkaline earth metal carbonate fine powder and cycloolefin resin are mixed in a predetermined ratio and premixed, and strands are produced using a twin-screw extruder. The kneading temperature can be, for example, 180 to 210°C, and the diameter of the strands can be 1 to 2 mm. Then, pellets having a length of 2 to 4 mm are produced from the strands using a pelletizer.

[0049] The obtained pellets are put into an injection molding machine and injection molded at a predetermined mold temperature to obtain a molded product. In the present invention, the temperature of the mold surface into which the resin flows in the injection molding machine is referred to as the mold temperature T. The mold temperature can generally be controlled to a predetermined temperature by setting the temperature of the injection molding machine itself.

[0050] For example, the mold temperature can be within a range of 50 to 130° C., and preferably 50 to 100° C. Furthermore, the resin temperature before being introduced into the mold during injection molding is not particularly limited, and can be appropriately selected within a range of, for example, 250 to 300° C., and preferably 255 to 265° C. For example, when the resin temperature is 260° C., the mold temperature can be 130° C.

[0051] The molded product may be, for example, a disk-shaped resin plate having a thickness of about 1 to 2 mm and a diameter of about 5 to 30 mm. The disk-shaped resin plate may have a convex upper surface. For example, the molded product may be a resin plate simulating an optical lens having a diameter of 30 mm, an edge thickness of 1.0 mm, and a center thickness of 1.5 mm.

[0052] The resin composition of the present invention exhibits particularly excellent effects when it contains strontium carbonate fine powder as an alkaline earth metal carbonate together with a cycloolefin copolymer, as described below. The strontium carbonate fine powder is needle-shaped and has negative birefringence in the long axis direction. When added to a resin, the strontium carbonate fine powder is aligned parallel to the orientation direction of the resin, thereby offsetting the positive birefringence of the resin.

[0053] Injection molded resin has a large expansion flow component perpendicular to the resin flow direction from the gate. In addition, when the molded shape is circular (lens shape), the range is even larger. It is presumed that this causes the strontium carbonate fine powder in the resin composition to have more components oriented perpendicular to the MD direction (direction in which the resin flows) of injection. On the other hand, since the birefringence of the resin is manifested by the stress generated in the surface layer where the temperature change is larger, the birefringence suppression effect of the strontium carbonate fine powder is difficult to manifest.

[0054] COP has a higher MFR value (a measure of melt fluidity) than COC. For this reason, it is assumed that the fluidity after injection is good, the ratio of expansion flow is large, and the orientation is likely to become random before the fluidity decreases due to cooling. Due to this, it is thought that COC is more likely to exhibit the birefringence suppression effect by adding strontium carbonate fine powder in injection molded products such as lens shapes.

[0055] An injection-molded article produced by injection molding the resin composition of the present invention containing a cycloolefin copolymer as a cycloolefin-based resin together with an alkaline earth metal carbonate can be effectively used as an optical component such as an optical resin lens, a camera module for a smartphone, or a cover sheet for an in-vehicle display.

[0056] The following supplementary notes are further disclosed regarding the above-described embodiment of the present invention.

[0057] <1> A resin composition containing an alkaline earth metal carbonate and a cycloolefin copolymer, wherein the content of the alkaline earth metal carbonate in the resin composition is 1.1 to 2.5 parts by mass per 100 parts by mass of the cycloolefin resin. <2> The alkaline earth metal carbonate comprises a fine powder of strontium carbonate and a surfactant attached to the surface of the fine powder of strontium carbonate. <1> The resin composition according to claim 1. <3> The aspect ratio of the strontium carbonate fine powder is 1.1 or more. <2> The resin composition according to claim 1. <4> The average diameter of the strontium carbonate fine powder is 10 nm or more and 100 nm or less. <2> or <3> The resin composition according to claim 1. <5> The above <1> ~ <4> 2. An optical member comprising an injection-molded article of the resin composition according to claim 1. EXAMPLES

[0058] Next, the present invention will be specifically described with reference to examples, but the present invention is not limited to the following examples.

[0059] As the alkaline earth metal carbonate fine powder, a strontium carbonate fine powder and a composite carbonate fine powder containing strontium and calcium were prepared. (Production of alkaline earth metal carbonate fine powder) (a) Reaction process 2440g of strontium hydroxide octahydrate (special grade reagent, purity: 96% or more) was added to 20L of pure water at a water temperature of 10°C, and mixed to prepare an aqueous suspension of strontium hydroxide with a concentration of 5.6% by mass. DL-tartaric acid (special grade reagent, purity: 99% or more) was added to this aqueous suspension of strontium hydroxide, and stirred to dissolve in the aqueous suspension. Next, while maintaining the liquid temperature of the aqueous suspension of strontium hydroxide at 10°C and continuing stirring, carbon dioxide gas was blown into the aqueous suspension at a flow rate of 3.3L / min (flow rate of 3mL / min per 1g of strontium hydroxide) until the pH of the aqueous suspension reached 7, generating strontium carbonate particles. Then, stirring was continued for another 30 minutes to obtain an aqueous suspension of strontium carbonate particles.

[0060] (b) Aging process The obtained aqueous suspension of strontium carbonate particles was placed in a stainless steel tank and heated at 80° C. for 24 hours to grow the strontium carbonate particles into needle-like shapes, and then allowed to cool to room temperature to produce an aqueous slurry of strontium carbonate particles.

[0061] (c) Surface treatment and drying process 3500g of strontium carbonate particle aqueous slurry (concentration: 5.8% by mass) was put into a homomixer (TK homomixer Mark II, manufactured by Primix Corporation), and 56.8g of polyoxyethylene styrenated phenyl ether phosphate was added to the aqueous slurry (28 parts by mass relative to 100 parts by mass of strontium carbonate particles) while stirring by rotating the stirring blade of the homomixer at a peripheral speed of 7.85 m / sec, and dissolved. Stirring and mixing were then continued for 1 hour. The aqueous slurry after stirring and mixing was dried to obtain surface-treated strontium carbonate fine powder (A-1). The obtained strontium carbonate fine powder was observed under an electron microscope, and it was confirmed to be a fine powder of needle-shaped particles (average major axis: 60 nm).

[0062] As the cycloolefin resin, a cycloolefin copolymer resin (Mitsui Chemicals' cycloolefin copolymer APL5014CL) was prepared. The glass transition temperature Tg of the cycloolefin resin used here is 135°C.

[0063] Example 1 A resin composition containing 2 parts by mass of fine strontium carbonate powder and 100 parts by mass of a cycloolefin copolymer resin was prepared, and a molded article was manufactured by injection molding using this composition. Specifically, 100 g of strontium carbonate fine powder and 10,000 g of cycloolefin copolymer resin (APL5014CL) were premixed and then a twin-screw extruder (manufactured by Berstorff) was used to produce strands with a diameter of 2 mm at a kneading temperature of 195° C. Then, a pelletizer was used to produce pellets with a length of 3 mm from the strands.

[0064] The obtained pellets were put into an injection molding machine manufactured by Meiho Co., Ltd. and injection molded under conditions of a resin temperature of 260°C and a mold temperature of 130°C to produce an injection molded product (a disc-shaped resin plate with a diameter of 30 mm, an end thickness of 1.0 mm, and a center thickness of 1.5 mm, simulating a convex optical lens) of Example 1. The mold temperature is the temperature of the mold surface into which the resin flows in the injection molding machine, and was controlled to a predetermined temperature by the temperature setting of the injection molding machine body.

[0065] Example 2 An injection-molded article of Example 2 was obtained in the same manner as in Example 1, except that the amount of strontium carbonate fine powder was changed to 1.25 parts by mass.

[0066] Example 3 An injection-molded article of Example 3 was obtained in the same manner as in Example 1, except that the amount of strontium carbonate fine powder was changed to 1.5 parts by mass.

[0067] Example 4 An injection-molded article of Example 4 was obtained in the same manner as in Example 1, except that the amount of strontium carbonate fine powder was changed to 1.75 parts by mass.

[0068] Example 5 An injection-molded product of Example 5 was obtained in the same manner as in Example 1, except that the amount of strontium carbonate fine powder was changed to 2.25 parts by mass.

[0069] Example 6 With reference to the examples in International Publication No. 2022 / 059650, Ca x Sr 1-x CO 3 We prepared fine particles of composite carbonate represented by (x=0.1, 0.2, 0.335). The crystal structure of the obtained composite carbonate was determined by XRD analysis, and the results are shown in Figure 1. x Sr 1-x CO 3The sample prepared with x=0.5 is a single aragonite phase, as shown in Fig. 1(a). In addition, a peak shift due to solid solution can be confirmed from Fig. 1(b). The presence of Ca was confirmed by EDS. On the other hand, the sample prepared with x=0.5 has a Ca x Sr 1-x CO 3 In addition to the aragonite phase, calcite was formed as a secondary phase. An injection-molded product of Example 6 was obtained in the same manner as in Example 4, except that the strontium carbonate fine particles were changed to composite carbonate fine particles with x=0.1.

[0070] Comparative Example 1 An injection-molded article of Comparative Example 1 was obtained in the same manner as in Example 1, except that the fine strontium carbonate powder was not mixed.

[0071] Comparative Example 2 An injection-molded article of Comparative Example 2 was obtained in the same manner as in Example 1, except that the amount of strontium carbonate fine powder was changed to 0.5 parts by mass.

[0072] Comparative Example 3 An injection-molded article of Comparative Example 3 was obtained in the same manner as in Example 1, except that the amount of strontium carbonate fine powder was changed to 1.0 part by mass without changing the amount of cycloolefin resin.

[0073] Comparative Example 4 An injection-molded article of Comparative Example 4 was obtained in the same manner as in Example 1, except that the amount of strontium carbonate fine powder was changed to 3.0 parts by mass without changing the amount of cycloolefin resin.

[0074] Comparative Example 5 An injection-molded product of Comparative Example 5 was obtained in the same manner as in Example 1, except that the amount of strontium carbonate fine powder was changed to 4.0 parts by mass without changing the amount of cycloolefin resin.

[0075] Comparative Example 6 An injection-molded product of Comparative Example 6 was obtained in the same manner as in Example 1, except that the type of cycloolefin resin was changed to cycloolefin polymer resin "RX4500" manufactured by JSR Corporation.

[0076] The physical properties of the injection molded articles of the Examples and Comparative Examples were examined as follows. Haze: Measured using a spectrophotometer (NDH4000, manufactured by Nippon Denshoku Industries Co., Ltd.). Birefringence (ΔNxy, ΔP): The in-plane retardation (retardation) Re and the out-of-plane retardation (retardation in the thickness direction / retardation in the thickness direction) Rth were measured using a phase measuring device (KOBRA-WR manufactured by Oji Scientific Instruments).

[0077] Here, the physical properties of the optical member will be described. Ideally, optical components (lenses, sheets, etc.) should not have birefringence, i.e., both the in-plane retardation (Re) and the out-of-plane retardation (Rth) should be zero. In particular, lenses with a small angle of incidence are required to have Re close to zero. Optical lenses used in general image sensors are made up of multiple lenses (usually 5 to 6 lenses), so it is desirable to have a configuration that can cancel out birefringence as a whole. Even if the birefringence in each lens is small, it will increase if it is in the same direction, so it may be effective to combine lenses that have partially negative values. The same is true for Rth, the more negative the value, the better. In the case of applications with a wide angle of incidence (such as cover sheets), it is possible to suppress the overall Rth by combining and laminating resins with negative values, and to suppress the deterioration of display quality due to the viewing angle. In other words, in order to obtain optical lenses that are used in general image sensors, a resin composition that is close to zero in both positive and negative values ​​is required.

[0078] The above phase measurement device measures the in-plane phase difference (retardation) R 0 and the phase difference (retardation) R measured by light incident on the measurement object at an incident angle of 40°. θThe out-of-plane retardation Rth is calculated from the thickness d (input value) of the object to be measured and the average refractive index Navr (input value) of the object to be measured. Here, in the examples and comparative examples described in this specification, the out-of-plane retardation Rth is defined by a value for light having a wavelength of 587.3 nm. The smaller the value, the lower the birefringence.

[0079] The results obtained are summarized in the table below, along with the resin composition and injection conditions. In order to equalize the effect of lens thickness, the in-plane retardation (Re) and out-of-plane retardation (Rth) are normalized to 100 μm.

[0080] [Table 1]

[0081] [Table 2]

[0082] As shown in the above table, when 1.1 to 2.5 parts by mass of strontium carbonate fine powder is contained per 100 parts by mass of cycloolefin copolymer, a molded article having low in-plane retardation (Re) and haze while maintaining a certain range of low out-of-plane retardation (Rth) is obtained. When a similar amount of composite carbonate in which part of strontium is replaced with calcium is contained, a molded article having low in-plane retardation (Re) and haze while maintaining a certain range of low out-of-plane retardation (Rth) is also obtained. In contrast, when the amount of strontium carbonate fine powder is less than 1.1 parts by mass relative to 100 parts by mass of cycloolefin copolymer, or exceeds 2.5 parts by mass relative to 100 parts by mass of cycloolefin copolymer, a molded article having low out-of-plane retardation (Rth), in-plane retardation (Re), and haze cannot be obtained. Similarly, when a cycloolefin polymer resin is used as the cycloolefin resin, a molded article having low out-of-plane retardation (Rth), in-plane retardation (Re), and haze cannot be obtained.

Claims

1. A resin composition containing an alkaline earth metal carbonate and a cycloolefin resin, the content of the alkaline earth metal carbonate in the resin composition is 1.1 parts by mass to 2.5 parts by mass per 100 parts by mass of the cycloolefin resin; The cycloolefin resin is a cycloolefin copolymer.

2. An optical member comprising an injection molded article made of the resin composition of claim 1.

Citation Information

Patent Citations

  • Optical member and image display device

    JP2021047402A

  • JP2236-242